Comprehensive Genomic Characterization of Tumor Microenvironment and Relevant Signature in Clear Cell Renal Cell Carcinoma - Zhang, Chuanjie; Qi, Feng; Zheng, Yuxiao; Xia, Xin; Li, Xiao; Wang, Xinwei (Frontiers in Oncology, 2022)
Purpose: To systematically investigate the characterization of tumor microenvironment (TME) in clear cell renal cell carcinoma (ccRCC), we integrated comprehensive analysis incorporating genomic alterations, cellular interactions, infiltrating immune cells or risk signature. Patients and Methods: Multi-omics data including RNA-seq, single nucleotide variants (SNV) data, copy number variation (CNV) data, miRNA and corresponding prognostic data were obtained from the Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) database. The CIBERSORT algorithm was utilized to identify prognostic TME subclusters, and TMEscore was further quantified. Moreover, the mutational landscape of TCGA-KIRC was explored. Lastly, TIDE resource was applied to assess the significance of TME-score in predicting immunotherapeutic benefits. Results: We analyzed the TME infiltration patterns from 621 ccRCC patients, and identified 5 specific TME subclusters associated with clinical outcomes. Then, we found the TME cluster 5 was significantly related to favorable prognosis and enriched memory B cell infiltration. Accordingly, we depicted the clustering landscape of TME clusters, TMEscore levels, tumor mutation burden (TMB), tumor grades, purity and ploidy in all patients. Lastly, TIDE was used to assess the efficiency of immune checkpoint blocker (ICB) and found the TMEscore possesses superior predictive significance than TMB, implicating its promising foreground to be an essential independent prognostic biomarker and drug indicator in clinical utility. Conclusions: Our study depicted the clustering landscape of TMEclusters, TMEscore levels, TMB, tumor grades, purity and ploidy in total ccRCC patients. The TMEscore was proved to possess promising significance for predicting prognosis and ICB responses, in accordance with the goal of developing rationally individualized therapeutic interventions.